Ajustamento conjugal em casais em que um dos cônjuges possui o diagnóstico de epilepsia - Bovério, Jussara Maria Simões (2016)
Epilepsy and its stigma can negatively affect life quality of patients and their families. Living with this chronic disease may interfere with the level of adjustment of couples. Objectives: To assess the level of adjustment of couples in which at least one spouse has a diagnosis of epilepsy. Patients and methods: 30 couples followed up at the outward epilepsy service at the medical college in São José do Rio Preto (FAMERP) São Paulo state, Brazil. The DYADICT ADJUSTMENT SCALE (DAS) and the Socioeconomical and Health Conditions Assessment Questionnaire have been used to collect data. Results: 96.6 % do not leave home after fighting, 93.3% rely on their spouse, 93.1 % agree with the decisions taken together, 92.9% never regret having married, 90% share goals and objectives, 90% show themselves adjusted to each other, 90% of couples always agree with the control of finance, 86.7% value time spent together, 82.1% deal well with parents and in-laws, 82% agree with friendships, 80.8% show love, 80.0% value household work, 79.3% have the same philosophy of life, 78.5% demonstrate affection and satisfaction, 76.9% agree sexually, 76% with religiosity, 75.9% agree with interests and social activities, 73.3% never think about their relationship, 71.4% do not talk over career plans, 66.7% never think about divorcing, 66.67% agree as to leisure activities, 63.3% each other’s customs, 62.1% laugh together, 53.3% share stimulating ideas, 51.9% devote to external interests together, 50.0% rarely fight, 48.3 % never pick on each other, 48.1% kiss their spouse every day, 46.2% are not tired for sex, 44.8% have easy conversation, 40.0% want much their relationship to work and they do everything possible for this to happen, 33.3% consider their relationship perfect, and 10% have shown not to be adjusted. Conclusion: The study has shown that epilepsy does not affect the level of marital adjustment.